Pengaruh Narasumber dan Saluran Komunikasi Terhadap Persepsi Mahasiswa - Letario Prodeo; Halomoan Harahap (Publikasi Indonesia, 2025)
This study aims to identify credible sources of information as well as communication channels used by Kalimantan students in receiving information about the palm oil industry for the 2023–2024 period. In addition, this study also describes the perception of Kalimantan students about the palm oil industry in Indonesia and analyzes the influence of resource persons and communication channels on this perception. This study uses a positivist paradigm with a descriptive and explanatory approach to analyze the data obtained through a questionnaire survey based on the Likert scale. The results of the study show that the credibility of the resource persons, especially researchers and academics, has a significant influence on student perception. Communication channels that support direct interaction, such as seminars or discussions, have proven to be more effective in forming a deeper perception of the palm oil industry. Theoretically, this research is expected to provide new insights into effective communication strategies, especially for issues related to the palm oil industry. Practically, the results of this study can be a reference for palm oil industry stakeholders in developing more relevant and effective communication strategies.